Fan Ties and Friendships: A Longitudinal Network Study of Division III Sports on Campus - Katz, Matthew; Cocieru, Ovidiu; Springer, Daniel; Dixon, Marlene (Journal of Intercollegiate Sport, 2021)
The purpose of this longitudinal actor-based network study is to examine the evolution of sport fan ties and friendship ties on Division III campuses. Using two years of network data from a cohort of new students at a Division III institution, a SIENA model is developed to empirically test the co-evolution of fan ties and friendship ties. Grounded in student development, sport consumer behavior, and network theories, the overarching goal of this study is to explore the causal effect of fan ties on friendship ties among new students. To ascertain the value of Division III sports on campus, the authors explore the role of sports on campus in promoting friendships for new students based on the strong theoretical tradition from student development highlighting the salience of peer relationship in student success and retention. Accordingly, theoretical implications related to sport fan networks are considered within practical discussion of Division III sports and retention.